“La ricerca della differenza”. Interventi e progetti fuori dal “sistema” nell’attività di Ugo La Pietra tra il 1967 e il 1973 - Sara Fontana (Annali Online dell'Università di Ferrara. Sezione Lettere)
This contribution focuses on a short section of the path of Ugo La Pietra (1967-1973), an eclectic and volcanic artist with sixty years of activity behind him. The article intends to enucleate some lines of analysis, chronologically and conceptually intertwined, resulting from his refusal to operate in the logic of systems imposed by a community and concretized in aesthetic operations able to decode the antinomies, while offering the tools to break the pre-established schemes. This action, announced since 1964, materialized a few years later with the “Debalancing system”, a theory developed on the wire of a continuous transfer from art to architecture, through the “Dives”, the reconnaissances on “Degrees of freedom”, the “Recovery” and “Reinvention” of objects, places and spaces, up to a methodical enhancement of traditional handycrafts, in the certainty that small movements can change reality and produce difference.